2004
DOI: 10.1039/b409071c
|View full text |Cite
|
Sign up to set email alerts
|

The formation of dimeric phosph(iii)azane macrocycles [{P(µ-NtBu)}2·LL]2[LL = organic spacer]

Abstract: The dimeric macrocycles [[P(mu-NtBu)]2.LL]2 [LL = OCH2C(Me)2CH2O (1), 2,6-(NH)2C5H3N (2), 1,2-(NH)2C6H4(3)] have been obtained by the reactions of the appropriate diols and diamines (LLH2) with the dimeric phosph(III)azane [ClP(mu-NtBu)]2. Under different conditions the reaction of 1,2-(NH2)2C6H4 with [ClP(mu-NtBu)]2 gives the monomer [[P(mu-NtBu)]2.[1,2-(NH)2C6H4]] (4) (instead of the dimer 3). Contrary to the literature, the results illustrate that the formation of dimeric macrocycles is common in these reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…The corresponding free energy of activation (Δ G ≠ ) for this process of 31 kJ mol −1 was found to be similar to that previously reported for oxygen‐bridged phosphazane macrocycles 25b…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The corresponding free energy of activation (Δ G ≠ ) for this process of 31 kJ mol −1 was found to be similar to that previously reported for oxygen‐bridged phosphazane macrocycles 25b…”
Section: Resultssupporting
confidence: 86%
“…Coordination of chiral cyclophosphazanes to metals : In the next step of the study we investigated the complexation behavior of the two phosphorus lone pairs of the CycloP ligands to several late transition metals, in particular to assess the rigidity of the chiral ligands upon metal coordination. This was an important issue because previous studies suggested that ansa cyclophosphazanes of this type could potentially oligomerize giving dimeric macrocyclic species,25b and the presence of Lewis acidic metal centers could also result in ring‐expansion 27…”
Section: Resultsmentioning
confidence: 99%
“…[40] Because compound 1 is soluble in the most non-protic organic solvents, it is the nature of the nucleophile that dictates the choice of the solvent. For instance, the reaction of compound 1 with o-phenylenediamine at room temperature in toluene/Et 3 Ns tirred for sixteen hours produces the dimeric macrocycle [{P(m-NtBu)} 2 {1,2-(NH) 2 C 6 H 4 }] 2 ;w hereas the heating compound 1 in THF/Et 3 Nt or eflux overnight results in the formation of the monomeric cyclic compound [{P(m-NtBu)} 2 {1,2-(NH) 2 C 6 H 4 }].…”
Section: Resultsmentioning
confidence: 99%
“…In the traditional syntheses of these species, the choice of the reaction conditions and solvents plays a crucial role in influencing the formation(s) of the reaction product(s). For instance, the reaction of compound 1 with o ‐phenylenediamine at room temperature in toluene/Et 3 N stirred for sixteen hours produces the dimeric macrocycle [{P(μ‐N t Bu)} 2 {1,2‐(NH) 2 C 6 H 4 }] 2 ; whereas the heating compound 1 in THF/Et 3 N to reflux overnight results in the formation of the monomeric cyclic compound [{P(μ‐N t Bu)} 2 {1,2‐(NH) 2 C 6 H 4 }] . Because compound 1 is soluble in the most non‐protic organic solvents, it is the nature of the nucleophile that dictates the choice of the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] Thevast majority of structures comprising P III atoms and/ or their applications have been based on disubstituted cyclodiphosphazane monomeric species (Figure 1, type m III ). [18,23,30] However,s everal acyclic( a)a nd cyclic (c)i norganic cyclodiphosphazane oligomeric species have been successfully synthesised and described in the literature (monomers,dimers,trimers,tetramers and pentamers,types m, d, t, tt and p,respectively,F igure 1). [14,31] Them ajority of the efforts made in cyclodiphosphazane chemistry have been focused on the synthesis of both hybrid and fully inorganic cyclic cyclodiphosphazane species due to their potential applications in host-guest chemistry.…”
Section: Introductionmentioning
confidence: 99%